The Evangelical Lutheran Church in Namibia (ELCIN) and poverty, with specific reference to semi-urban communities in Northern Namibia : a practical theological evaluation - Niitenge, Gideon (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.